AN ALYSIS OF ECONOMIC EFFICINCY AND OPTIMAL ALLOCATION OF ECONOMIC RESOURCES IN ABU GHRAIB DAIRY FACTORY USING LINEAR PROGRAMMING IN 2015 - & Ali, Fahd (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The resource allocation and planning is one of most important issues in the field of administration because of its importance role could be played in raising the factory performance and to create the conditions and means for the advancement of its reality so the goal of research is to reach mix of commodity through re-allocation of resources between the various production lines which is achieved with it maximum profit margin and this optimum plant was done through collection of data from dairy Abu Ghraib factory in 2015 and adopted win QSB program to find the optimal production plan it shows the reality of factory production that loses 1,755,486,044 dinars, and when we make the basic shows it is investigating profit increased by 1,046,003,000 dinars shows that there is a surplus in the work item (93%) by you make attempts on the basic plan emerged from three alternative plans the most important of the third alternative plan - b - achieved a profit by 28,090,890,000 dinar total profit for the basic plan exceeds by 27,004,887,000 dinars decreased surplus in the work item to 24%, and when you perform a sensitivity analysis to see changes show that in the case of high variable costs by 10% has been no change in the results of the basic plan, but profit dropped for profit basis the plan by 104.6 million dinars, while in the case of high variable costs by 10% with low prices by 10% has also been some of the activities excluded which caused a loss in the target and reduced the amount of production of the quantity cream in the base plan by 196.817 tons function as some productive activities that did not appear in the basic plan emerged was this plain achieved an increase in gross profit amounted to 438.656 million dinars for the base plan, but in the case of high product prices 10% did not any change on the result of the basic plain occurs because the change at the same rate for all products was the plan achieved an increase in profit exceeds the profit for the basic plan by 104.6 million dinars, it was concluded research that the factory does not follow the scientific metod in management and there are worse in the allocation of resources and a large waste the resources for such research recommend to adopt scientific method, especially linear programming method available in the factory resource planning application for optimum productivity plans that would lead to expand the plant to increase production and profits as well as lead to the optimal allocation of economic resource available.